What can we learn from more than 1,000 Brazilian patients at risk of hereditary cancer? - Leite, Ana Carolina Rathsam; Suzuki, Daniele Assad; Pereira, Allan Anderson Lima; Machado, Natalia Polidorio; Barroso-Sousa, Romualdo; Correa, Tatiana Strava; Moura, Fernanda Cesar; Morbeck, Igor Alexandre Protzner; Gumz, Brenda Pires; Faria, Luiza Dib Batista Bugiato; Fernandes, Gustavo dos Santos; Sandoval, Renata Lazari (Frontiers in Oncology, 2022)
Identifying individuals at a higher risk of developing cancer is a major concern for healthcare providers. Cancer predisposition syndromes (CPS) are the underlying cause of cancer aggregation and young-onset tumors in many families. Germline genetic testing is underused due to lack of access, but Brazilian germline data associated with CPS are needed. Methods: Medical records of patients referred for genetic counseling at the Oncogenetics Department from 2017 to 2021 were reviewed. The clinical features and germline findings were described. Detection rates of germline pathogenic/likely pathogenic variant (P/LPV) carriers were compared between international and Brazilian guidelines for genetic testing. Results: A total of 1,091 individuals from 985 families were included in this study. Most patients had a family history of cancer, including 64% with a family member under 50 with cancer. Sixty-six percent of patients had a personal history of cancer. Young-onset cancers represented 62% of the patients affected by cancer and 17% had multiple primary cancers. The cohort included patients with 30 different cancer subtypes. Breast cancer was the most prevalent type of cancer (52.6%). Germline testing included multigene panel and family variant testing. Approximately 27% of the tested patients harbored germline P/LPVs in cancer susceptibility genes. BRCA2, BRCA1, and TP53 were the most frequently reported genes, corresponding to 18.6%, 14.4%, and 13.5% of the positive results, respectively. Genetic testing criteria from international guidelines were more effective in identifying carriers than the Brazilian National Agency of Supplementary Health (ANS) criteria (92% vs. 72%, p<0.001). Forty-six percent of the cancer-unaffected patients who harbored a germline P/LPV (45/98) would not be eligible for genetic testing according to ANS because they did not have a family variant previously identified in a cancer-affected relative. Conclusion: The high detection rate of P/LPVs in the present study is possibly related to the genetic testing approach with multigene panels and cohort’s characteristics, represented mainly by individuals with a personal or family history of young-onset cancer. Testing asymptomatic individuals with suspicious family history may also have contributed to a higher detection rate. A significant number of carriers would not have been identified using ANS criteria for genetic testing.